Interaction between Nonsteroidal Anti-inflammatory Drugs and Low-fat Dietary Intervention on Colorectal Cancer Incidence; the Women's Health Initiative (WHI) Dietary Modification Trial. (18th August 2017) - Kato, Ikuko; Lane, Dorothy; Womack, Catherine R.; Bock, Cathryn H.; Hou, Lifang; Lin, Jennifer H.; Wu, Chunyuan; Beebe Dimmer, Jennifer; Simon, Michael S.
ABSTRACT: Background : The Women's Health Initiative (WHI) Dietary Modification (DM) trial did not show that reductions in dietary fat accompanied by increases in vegetable and fruit consumption decrease the incidence of colorectal cancer. Secondary analyses suggested that aspirin use may modify the intervention effects of DM on colorectal cancer development, although a recent reanalysis including the postintervention period confirmed no main effect of the intervention on reducing colorectal cancer incidence Methods : We analyzed data from 48, 834 postmenopausal women who were randomized into the low-fat DM ( N = 19, 540) or comparison ( N = 29, 294) group for an average 8.1 years and followed for an additional 9.4 years through August 31, 2014. Exposure to specific class(es) or strength(s) of nonsteroidal anti-inflammatory drugs (NSAIDs) was modeled at baseline and as time-dependent use through the 9-year clinic visit. A Cox proportional hazard model was employed to assess the association of the DM, medication use, and their interaction with colorectal cancer events. Results : A total of 906 incident cases of colorectal cancer were identified during the intervention and postintervention periods. By both exposure models, we found that colorectal cancer incidence was not different in the DM from the comparison group among any type of NSAID users. None of the interactions with any category of NSAID use was statistically significant; however there was most modest evidence for an interaction ( p = 0.07) with aspirin use at baseline (hazard ratio [HR] = 0.81, 95% confidence interval [CI], 0.60–1.11 for users; HR = 1.12, 95% CI, 0.97–1.30 for nonusers). Strength and duration of aspirin use at baseline did not alter the associations. Conclusion : Extended follow-up of women in the WHI DM trial did not confirm combined protective effects of aspirin and low-fat diet on colorectal cancer risk among the postmenopausal women.